Dirichlet Theorem for Jacobi-Dunkl Expansions. (29th December 2020) - Chouchene, Frej; Haouala, Iness
Abstract: The purpose of this paper is to study the pointwise convergence of the Jacobi-Dunkl series. We establish a Dirichlet type theorem for expansions in term of Jacobi-Dunkl polynomials.